Isolated Pituitary Metastasis of Renal Cell Carcinoma: A Case Report and Systematic Review of the Literature - Öven, Bala Başak; Demir, Mustafa K.; Çelik, Serkan; Moujawaz, Riad; Somay, Adnan; Kılıc, Turker (Current Medical Imaging, 2022)
Background: Isolated pituitary gland metastasis is an extremely rare event in renal cell carcinoma. We present a unique case of isolated pituitary metastasis of renal cell carcinoma and a systematic review of literature on it. Case Report: In this case, an abdominal ultrasound in an asymptomatic 51-year-old female patient showed a mass in her left kidney. Radical nephrectomy was performed and the tumor was diagnosed as a stage 1 clear cell carcinoma. Throughout the 3 months of the follow-up period, the patient started complaining of visual disturbances and headaches. A pituitary mass was found on brain magnetic resonance imaging and was suspected to be a macroadenoma. Surgical resection of the tumor was performed and the final pathological diagnosis was made as a pituitary metastasis of the renal cell carcinoma. After surgery, radiotherapy with sunitinib, a receptor tyrosine inhibitor, was performed. Conclusion: The clinical symptoms are usually related to the mass effect of the tumor and anterior pituitary involvement. Most of the cases mimic pituitary macroadenoma on MRI. The most preferred treatment combination is surgery and radiotherapy. We recommend adding sunitinib to this combination. This illustrative case and those found in a systematic review of the literature highlight the importance of histopathologic diagnosis and appropriate management since isolated pituitary metastasis is challenging to preoperative diagnosis.
Keywords: renal cell carcinoma